Contribution of irradiation-induced defects to hardening of a low-copper reactor pressure vessel steel. (15th August 2018) - Shimodaira, Masaki; Toyama, Takeshi; Yoshida, Kenta; Inoue, Koji; Ebisawa, Naoki; Tomura, Keiko; Yoshiie, Toshimasa; Konstantinović, Milan J.; Gérard, Robert; Nagai, Yasuyoshi
Abstract: We investigated the fluence dependence of irradiation-induced solute cluster, dislocation loop, and very small defect to reveal the hardening mechanism in surveillance test specimens from a reactor pressure vessel steel with low-Cu content (0.04 wt%) using atom probe tomography (APT), weak-beam scanning transmission electron microscopy (WB-STEM), and positron annihilation spectroscopy. A high number density (>10 23 m −3 ) of solute clusters mainly composed of Ni, Mn, and Si atoms were found in highly neutron irradiated specimens (∼10 24 neutrons m −2 ( E > 1 MeV)) by APT. These solute clusters were one of the main sources of hardening as reported previously. On the other hand, it was also revealed that dislocation loops were formed with a number density of ∼10 22 m −3 in the high-fluence specimens by WB-STEM. The estimated hardening due to dislocation loops was more than half of the actual hardening, showing that dislocation loops are also main source of irradiation hardening at high neutron fluence with the solid experimental evidences. Regarding specimens subjected to a low neutron fluence (∼10 23 neutrons m −2 ), very small defects, not detected by either WB-STEM or APT, were formed by positron annihilation spectroscopy. This result suggested that, at a low neutron fluence, the defects were the initial hardening source and they may grow the dislocation loops observed by WB-STEM at high fluence range. Graphical abstract: Image 1